A scoping review of the role of primary care providers and primary care-based interventions in the treatment of pediatric eating disorders. Issue 1 (2nd January 2020) - Lenton-Brym, T.; Rodrigues, A.; Johnson, N.; Couturier, J.; Toulany, A.
ABSTRACT: Youth with eating disorders are often cared for by specialized interdisciplinary teams in pediatric tertiary care centers. Enhanced involvement of primary care providers may provide added benefits to patients because it offers improved access, better continuity of care, and possibly less financial burden. This paper aims to synthesize and assess the literature on the role of the primary care provider in treating pediatric eating disorders in order to identify an optimal model of shared care. Sources were identified by entering search terms in 10 databases. Eligible sources were English publications focusing on primary care-based interventions for eating disorders in youth (=<24 years). The search yielded 5, 516 unique citations. Of these, 61 were ultimately included. Sources fell into two categories: (1) primary research (n = 3) and (2) reviews with recommendations for primary care providers (n = 58). The primary studies considered the primary care provider conducting behavioral therapy and guided self-help. Review articles suggested providing education, assessing for hospitalization, aiding in weight restoration, managing complications, referring, and coordinating care. Limited evidence exists that can guide effective primary care-based interventions for the treatment of pediatric eating disorders. Further research is needed to develop and evaluate interventions for the treatment of pediatric eating disorders in primary care settings so that best practices can be identified.